Latent fingerprint detection and identification using yellow-emitting YOF:Pr3+ nanophosphor - Sumedha Tamboli; Govind B. Nair; S.J. Dhoble; H.C. Swart (Optical Materials: X)
In this study, YOF:Pr3+ nanophosphors were synthesized using the microwave-assisted hydrothermal route. The structural and morphological properties of the nanophosphors calcined at different temperatures were studied in detail to optimize the synthesis conditions. The visible region and near-infrared (NIR) photoluminescence (PL) properties of the nanophosphors were obtained. Intense emission bands were observed in the blue and red regions under 250 nm excitation. The CIE chromaticity diagram showed that the color coordinates of the nanophosphors were located in the yellow region. The optimum Pr3+-concentration was found to be 0.002 mol fraction. The application of YOF: 0.002 Pr3+ nanophosphor for latent fingerprint detection was examined and evaluated on different types of surfaces. The nanophosphor demonstrated excellent adherence to the ridge patterns and sufficient sensitivity required for distinguishing between the ridges and the furrows. Different levels of detail were also observed that provided necessary information for the individualization of the fingerprints. The results suggest that the prepared YOF:Pr3+ nanophosphor can be a potential candidate for the rapid visualization and detection of latent fingerprints.